TRANSFORMATION OF EDUCATIONAL SUPERVISION WITH DIGITAL TECHNOLOGY: IMPLEMENTATION, OPPORTUNITIES AND CHALLENGES - Astuti, Ruli; Sutiah, Sutiah; Hidayatulloh; Nisak, Nur Maslikhatun (Academic Journal Research, 2024)
Technological developments in the field of education pose challenges for teachers and school leaders. Rapid adaptation to change and increased professionalism and commitment are the keys to the success of education. Digital academic supervision emerged as a solution to overcome the weaknesses of conventional supervisors, that are often time-controlled and effective. This article aims to study the implementation of the use of digital technology in education supervision as well as identify opportunities and challenges. The study uses the Systematic Literature Review (SLR) to examine the implementation of digital technology in the supervision of education by analyzing 12 articles published between 2020-2023. The results show that digital supervisors can facilitate supervisory implementation and effectively improve teacher competence. The challenges faced by digital supervision include limited internet access, minimal technology mastery by senior teachers, and the need for adequate support. Implementation of digital academic supervision is an important step towards improving the professionalism of teachers and the quality of education as a whole, on the condition of adequate training, improved access to technology, and support from all stakeholders.